As Bad as it Gets: How Climate Damage Functions Affect Growth and the Social Cost of Carbon - Lucas Bretschger; Aimilia Pattakou (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
The paper analyzes the effects of varying climate impacts on the social cost of carbon and economic growth. We use polynomial damage functions in a model of an endogenously growing two-sector economy. The framework includes nonrenewable natural resources which cause greenhouse gas emissions; pollution stock harms capital and reduces economic growth. We find a big effect of the selected damage function on the social cost of carbon and a significant impact on the growth rate. In our calibration a quartic damage function raises the social cost of carbon by more than a factor of ten compared to the linear function. In the social optimum the growth rate remains positive even when the damage function is highly convex. We test the robustness of the results by adding pollution decay and lowering the elasticity of intertemporal substitution which does not alter our results. We find that high marginal climate damages require stringent climate policies but do not preclude positive economic growth despite convexity, provided that policies are designed in an efficient manner.
Keywords: Q43; O47; Q56; O41; 330; Climate damages; social cost of carbon; endogenous growth; polynomial functions